2015
DOI: 10.1016/j.spl.2015.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Variance estimation in ranked set sampling using a concomitant variable

Abstract: Abstract:We propose a nonparametric variance estimator when ranked set sampling (RSS) and judgment post stratification (JPS) are applied by measuring a concomitant variable. Our proposed estimator is obtained by conditioning on observed concomitant values and using nonparametric kernel regression.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Their estimator was obtained by conditioning on observed concomitant values and using nonparametric kernel regression. Zamanzade and Vock [22]'s simulation results indicated that their proposed estimator considerably improves the estimation of variance when the rankings are fairly good. However, since our interest here is not about using values of concomitant variable, we do not consider their estimator for more investigations.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Their estimator was obtained by conditioning on observed concomitant values and using nonparametric kernel regression. Zamanzade and Vock [22]'s simulation results indicated that their proposed estimator considerably improves the estimation of variance when the rankings are fairly good. However, since our interest here is not about using values of concomitant variable, we do not consider their estimator for more investigations.…”
Section: Introductionmentioning
confidence: 98%
“…They showed that this estimator is more efficient than S Another estimator of variance when the RSS is applied by measuring a concomitant variable is proposed by Zamanzade and Vock [22]. Their estimator was obtained by conditioning on observed concomitant values and using nonparametric kernel regression.…”
Section: Introductionmentioning
confidence: 99%
“…Stokes and Sager [11] considered the problem of estimating the cumulative distribution function (CDF), and proved that RSS CDF estimator is more efficient than its counterpart in SRS regardless of the ranking quality. Stokes [10], MacEachern et al [7] and Zamanzade and Vock [16] proposed some variance estimators based on a ranked set sample. As the ranking process in RSS is performed without obtaining precise values of the sample units, it may not to be accurate (perfect).…”
Section: Introductionmentioning
confidence: 99%
“…Frey [3] and Li and Balakrishnan [5] proposed some nonparametric tests for assessing perfect ranking assumption which were followed by Vock and Balakrishnan [13], Zamanzade et al [14] and Zamanzade et al [15]. The problem of estimating the population mean and variance when RSS is applied by measuring a concomitant variable were discussed by Frey [4], Zamanzade and Mohammadi [17] and Zamanzade and Vock [16]. In this work, we plan to develop a more efficient CDF estimator when judgment ranking is performed using a concomitant variable.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the problem of estimation of a distribution function has been considered by Stokes and Sager (1988), Kvam and Samaniego (1994), and Duembgen and Zamanzade (2013). Stokes (1980), MacEachern et al (2002), Perron and Sinha (2004) and Zamanzade and Vock (2015) considered the problem of nonparametric estimation of variance. Ratio estimator for the population mean using ranked set sampling has been addressed by Kadilar et al (2009), andLi et al (2012) analysed rounded ranked set sample data.…”
Section: Introductionmentioning
confidence: 99%